A educação no processo de trabalho da enfermagem: o caso do hospital de ensino - Cavalcante, Elisângela Franco de Oliveira (2007)
It is in the work environment that occurs the relations of production, economy, personal development and professional growth. Thus, this environment characterizes for being a propitious way to the intellectual development diligent them. In this context, this study it had as objective to analyze the possibilities and challenges of the education to consist integrant part of the process of work of the nursing, in an education hospital. One is about a research of analytical matrix and qualitative boarding, that had as collaborating fifteen professionals of the nursing, middle- and upper-level, of a hospital of education in Natal/RN. It followed the metodológicos estimated ones of the thematic verbal history, which looks for to promote the agreement or clarification of determined situations, catching experiences of made use people to say on aspects of its life, keeping a commitment with the social context. The information then had been gotten by means of a research instrument that made possible the accomplishment of interviews, which had been marked anticipatedly and counted on the assent of that in they had participated. The interviews had been recorded in proper equipment, so that you say them of the collaborators transcribing and they were analyzed with the support of pertinent literature. The content of you say them was classified in empirical categories, as the nuclei of felt that they presented. With the analysis of the data, one evidenced that the education in the process of work of the nursing is something possible to occur, but that diverse they are the challenges that the same one has that to face to promote this phenomenon in its daily one of work. The collaborators had affirmed that the worker is necessary to remain itself permanently in study so that, thus, it grows professionally and improves its assistance. They had still affirmed that she is possible to work and to study, but that this requires determination of who intends such intention. E also guarantees that the diverse forms of education directed toward the care in nursing can have resolution, since that has collective compromising of the institution. This, as education hospital, recognizes to be necessary to possess one politics of education for its workers and is if considering implementation the same one through a structuralized program already. Therefore, the results of this research show the necessity of changes in the current scene where if they find the workers of nursing of the institution in study. These changes can be reached through one politics of investment in the workers, allowing, beyond other benefits, the reach of new knowledge that take them to a significant learning in favor of the population, reflecting in the quality of the given assistance